2000
DOI: 10.1002/etc.5620190623
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of micronuclei in bank voles from zones of high radiation at Chornobyl, Ukraine

Abstract: A population of Clethrionomys glareolus (bank vole) from a highly radioactive area within the Chornobyl, Ukraine exclusion zone was sampled in June 1997 and in June and October 1998. Internal radiation doses from radiocesium were estimated to be as high as 8 rads/d. Total dose, which takes into account the internal dose from radiostrontium and the surrounding environment, was estimated to be 15 to 20 rads/d. In contrast, individuals from a reference population lying outside of the exclusion zone registered neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 22 publications
2
22
1
Order By: Relevance
“…Over large areas, small mammals at Chornobyl are exposed to both internal and external radiation from 137 Cs and 90 Sr at a dose rate of about 32.6 mGy/d , with some individuals exposed to very high doses (Oleksyk et al, 2002). Biomedical studies of bank voles (Clethrionomys glareolus) have failed to detect any effects at these levels of exposure (Rodgers and Baker, 2000). These investigations have greatly extended the range of conditions under which wild rodents have been studied in contaminated areas (Turner, 1975;Arthur et al, 1986;Thomas, 2000;Rodgers et al, 2001).…”
Section: Chronic Radiation Exposure Of Wild Populations Of Rodentsmentioning
confidence: 99%
“…Over large areas, small mammals at Chornobyl are exposed to both internal and external radiation from 137 Cs and 90 Sr at a dose rate of about 32.6 mGy/d , with some individuals exposed to very high doses (Oleksyk et al, 2002). Biomedical studies of bank voles (Clethrionomys glareolus) have failed to detect any effects at these levels of exposure (Rodgers and Baker, 2000). These investigations have greatly extended the range of conditions under which wild rodents have been studied in contaminated areas (Turner, 1975;Arthur et al, 1986;Thomas, 2000;Rodgers et al, 2001).…”
Section: Chronic Radiation Exposure Of Wild Populations Of Rodentsmentioning
confidence: 99%
“…Reduced expression of the Mre11 gene often leads to genomic instability, and increased protein levels of ATM and MRE11 in some tumors are associated with resistance against radiotherapy (Tribius et al, 2001;Deng et al, 2011). An apparently low frequency of micronuclei in bank voles from the CEZ might indicate that this species has some degree of radioresistance (Rodgers and Baker, 2000). Given our results, Atm and Mre11 represent important candidate genes that regulate genomic stability in bank voles exposed to environmental radionuclides.…”
Section: Discussionmentioning
confidence: 57%
“…The bank vole is abundant (typically 10-80 animals per hectare) in forest habitats in much of Europe and Asia (Hutterer et al, 2016) and was one of the first mammals to re-colonize the CEZ after the nuclear accident (Baker et al, 1996). Bank voles inhabiting the CEZ show an increased frequency of chromosomal aberrations (Goncharova and Ryabokon, 1995) and increased oxidative stress in the form of cataracts (Lehmann et al, 2016), although estimates of DNA damage have returned conflicting results (Cristaldi et al, 1991;Rodgers and Baker, 2000). We hypothesize that exposure to low-dose IR stimulates the expression of key genes in the DDR pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that native rodent species (Clethrionomys glareolus, Apodemus sp., Microtus sp.) resident in the most radioactive regions near Chornobyl do not demonstrate statistically significant increases in their levels of mitochondrial DNA heteroplasmy, micronuclei (MN) formation, or chromosomal aberrations [4][5][6] when compared to the same species collected in regions of low contamination. Comparative data sets on strains of laboratory mice would be valuable in the application of these results to human health risks and the establishment of regulatory statutes.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to accurately estimate risk and to monitor levels of environmental radiation contamination by using wildlife species as sentinels [6,[8][9][10][11][12][13]. Although wildlife studies have contributed to our understanding of the ecological * To whom correspondence may be addressed (brodgers@ttu.edu).…”
Section: Introductionmentioning
confidence: 99%